A nurse‐led intervention improved blood‐borne virus testing and vaccination in Victorian prisons. (23rd October 2016) - Winter, Rebecca J.; White, Bethany; Kinner, Stuart A.; Stoové, Mark; Guy, Rebecca; Hellard, Margaret E.
Abstract: Objectives: Testing is the first step in treatment and care for blood‐borne viruses (BBVs) and sexually transmitted infections (STIs). As new treatments for viral hepatitis emerge, it is important to document effective models for BBV/STI testing. A nurse‐led intervention was implemented across three prisons in Victoria to improve BBV/STI testing. We evaluated the impact of the intervention on BBV/STI testing rates and hepatitis B (HBV) vaccination for reception prisoners. Methods: BBV/STI testing and HBV vaccination data were collected from the medical files of 100 consecutive reception prisoners at three prisons (n=300) prior to and after the intervention was implemented. Results: BBV testing increased significantly from 21% of prisoners to 62% post‐intervention. Testing for some STIs increased significantly, but remained low: 5% to 17% for chlamydia and 1% to 5% for gonorrhoea. HBV vaccination increased significantly from 2% to 19%. Conclusions: The nurse‐led intervention resulted in substantially increased testing and vaccination, demonstrating the benefits of a concerted effort to improve BBV and STI management in correctional settings. Implications: The availability of new treatments for hepatitis C has precipitated expansion of treatment in prisons. Improving the testing rate of prisoners, the first step in the treatment cascade, will maximise the benefits.